2016
DOI: 10.1038/srep38502
|View full text |Cite
|
Sign up to set email alerts
|

c-MET as a Potential Therapeutic Target in Ovarian Clear Cell Carcinoma

Abstract: In this study, we investigated the therapeutic effects of c-MET inhibition in ovarian clear cell carcinoma (OCCC). Expression levels of c-MET in the epithelial ovarian cancers (EOCs) and normal ovarian tissues were evaluated using real-time PCR. To test the effects of c-MET inhibitors in OCCC cell lines, we performed MTT and apoptosis assays. We used Western blots to evaluate the expression of c-MET and its down-stream pathway. In vivo experiments were performed to test the effects of c-MET inhibitor on tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 41 publications
1
29
0
Order By: Relevance
“…The IC 50 values of cCCC and oHGSC were 1.7 μmol/L and >10 μmol/L, respectively (Figure D). Considering that IC 50 values of ES2 and RMG1, ovarian CCC cell lines with MET overexpression, were 5 μmol/L and 3 μmol/L, respectively, it is likely that the cCCC organoids are sensitive to SU11274, and thereby suggestive of addiction to MET.…”
Section: Resultsmentioning
confidence: 99%
“…The IC 50 values of cCCC and oHGSC were 1.7 μmol/L and >10 μmol/L, respectively (Figure D). Considering that IC 50 values of ES2 and RMG1, ovarian CCC cell lines with MET overexpression, were 5 μmol/L and 3 μmol/L, respectively, it is likely that the cCCC organoids are sensitive to SU11274, and thereby suggestive of addiction to MET.…”
Section: Resultsmentioning
confidence: 99%
“…49 An in vitro study has shown that by treating OC cells with c-Met inhibitors, cell proliferation has been significantly reduced and increased apoptosis of cancer cells was observed. 50 A class of transcription factors known as specific proteins (Sp) regulates VEGF (vascular endothelial growth factor) expression with functional variation. Thus, Sp transcription factors have crucial impact on tumor expansion and metastasis.…”
Section: And Targeted Therapymentioning
confidence: 99%
“…Tumors were fixed in formalin and embedded in paraffin or snap-frozen in OCT compound (Sakura Finetek Japan, Tokyo, Japan) in liquid nitrogen. Using tumor tissues harvested from the in vivo experiments, IHC staining was done for Ki-67 (NOVUS, NB 600e1252), and TUNEL assays were performed using the ApopTag Peroxidase in situ Apoptosis kit as described previously [24].…”
Section: Animal Care and Development Of In Vivo Models Using Establismentioning
confidence: 99%